Effect of Cu Alloying on S Poisoning of Ni Surfaces and Nanoparticle Morphologies Using Ab-Initio Thermodynamics Calculations - Kim, Ji-Su; Kim, Byung-Kook; Kim, Yeong-Cheol (AMER SCIENTIFIC PUBLISHERS, 2015)
We investigated the effect of Cu alloying on S poisoning of Ni surfaces and nanoparticle morphologies using ab-initio thermodynamics calculations. Based on the Cu segregation energy and the S adsorption energy, the surface energy and nanoparticle morphology of pure Ni, pure Cu, and NiCu alloys were evaluated as functions of the chemical potential of S and the surface orientations of (100), (110), and (111). The constructed nanoparticle morphology was varied as a function of chemical potential of S. We find that the Cu added to Ni for NiCu alloys is strongly segregated into the top surface, and increases the S tolerance of the NiCu nanoparticles.
Keywords: TOTAL-ENERGY CALCULATIONS; SOFC ANODE; HYDROGEN-PRODUCTION; CATALYTIC-ACTIVITY; SEGREGATION; METALS; GAS